Performance of steel slag and steel sludge in concrete. (1st February 2016) - Roslan, Nurul Hidayah; Ismail, Mohammad; Abdul-Majid, Zaiton; Ghoreishiamiri, Seyedmojtaba; Muhammad, Bala
Highlights: We investigated the performance of steel slag and steel sludge in concrete. Pozzolanic properties of steel slag and steel sludge were evaluated. Inclusion of steel slag and sludge into concrete improve its properties. Up to 20% steel slag and 15% steel sludge could be used in concrete. Abstract: The impact of environmental cleansing through inclusion of hazardous wastes in cement related products cannot be overemphasized. This paper presents outcomes of laboratory experiments on the utilizations of electric arc furnace steel slag and steel sludge (by-products from steel making industries) as cement replacements in concrete. Pozzolanic properties of steel slag and steel sludge were evaluated using pozzolanic activity test specified by ASTMC618 . In addition, the materials were subjected to X-ray Fluorescence and X-ray Diffraction tests in order to identify their chemical as well as mineral compositions respectively. In the process, conductivity of materials suspension in calcium hydroxide (Ca(OH)2 ) solution were monitored. Mechanical properties of the concrete containing the steel slag and steel sludge were also evaluated. The results of pozzolanic activity tests show that steel sludge has a higher reactivity due its higher loss of conductivity which is about 72.9% as against 43.3% for steel slag. However, both materials show good reactivity in Ca(OH)2 solution. In fact, the strength activity index of both materials were observed to reach a minimum of 75% based on ASTMC618 requirement. Eventually, compressive strength development in concrete due to inclusion of 15% and 20% steel sludge and steel slag respectively yielded higher strength gains over the control mix particularly at later curing ages.